Correlation between milk suckled and growth of calves of ogaden cattle at one, three and six months of age, east Ethiopia - Mummed, Yesihak Yusuf (Springer International Publishing, 2013)
This study was conducted with the aim to evaluate correlation between milk suckled and growth of calves of Ogaden cattle managed in Beef farm at Harmaya University, eastern Ethiopia. Data was collected by a method of weight-suckle-weight once in a week from 269 calves born from 1994 to 2004. Weight of calves at birth, first, third and sixth months of age were 21.5 ± 3.3, 36.3 ± 4.4, 57.4 ± 11.0 and 91.7 ± 14.7 kg (mean ± SD). The daily weight gain of calves to first, third and six months of age were 0.5 ± 0.1, 0.4 ± 0.1 and 0.4 ± 0.1 kg day(-1), respectively. The amount of milk suckled to first, third and six months of age were 5.0 ± 1.2, 4.6 ± 1.1 and 2.7 ± 0.7 kg day(-1). The milk conversion efficiency to a kg body weight at first and third months of age was 10.2 ± 2.5 and 11.6 ± 2.9, respectively. Correlation between birth weight and daily milk suckled at one, three and six months of age were 0.34 (P< 0.001), 0.22 (P< 0.001) and 0.26 (P<0.05), respectively. The correlation between weight (1 and 3 months) and daily milk suckled at first and third months of age were positive with correlation value of 0.45 (P< 0.001) and 0.43 (P< 0.001), respectively. Correlation between weight change (1 and 3 months) and daily milk suckled at first and third months of age were 0.41 (P< 0.001) and 0.38 (P< 0.001), respectively. Positive association was observed between daily weigh gain and daily milk suckled at first and third months of age with correlation value of 0.44 (P< 0.001) and 0.29 (P< 0.001), respectively. Weight at three months was significantly correlated (P< 0.001) to weight at four, five and six months of age with correlation value of 0.65, 0.63 and 0.53, respectively. The significant correlation between milk suckled and weight at three months; and weight at three months and weight at weaning indicate significant role of milk in determining weaning weight of Ogaden cattle.